High performance, top-emitting, quantum dot light-emitting diodes with all solution-processed functional layers. Issue 35 (29th August 2017) - Tang, Zhaobing; Lin, Jie; Wang, Lishuang; Lv, Ying; Hu, Yongsheng; Fan, Yi; Guo, Xiaoyang; Zhao, Jialong; Wang, Yunjun; Liu, Xingyuan
Abstract : High performance top-emitting green quantum dot light-emitting diodes have been developed based on an all-solution process and with a bottom Al anode. Abstract : We report all solution-processed manufacture of high performance top-emitting (TE) quantum dot light-emitting diodes (QLEDs) with an aluminum (Al) film as bottom electrode and a homogeneous molybdenum oxide (MoO3 ) film as hole injection layer deposited on top of Al from water solution. With an optimal organic light outcoupling layer over the top electrode to depress the multiple light beam interference effect, the QLEDs show a maximum luminance and current efficiency of 151 000 cd m −2 and 33.7 cd A −1, respectively, attaining a nearly Lambertian light source. Especially, they exhibit a maximum external quantum efficiency of 7.4%. All solution-processed fabrication of these TE QLEDs is further implemented on some active light display samples of Arabic numerals with 15 × 15 mm 2 active area. The resulting simple passive matrix quantum dot light emitting displays possess excellent photoelectric characteristics, which represents a step toward practical application.